The microvascular reconstruction in children with maxillofacial defects: A Systematic Review - Violetti Valentin; Ratna Rayeni Natasha Roosseno (DiscoverSys Inc., 2022)
Background: Facial bones trauma in the pediatric population is linked to severe damage and impairment, particularly in maxillofacial, particularly in area. In addition, reconstruction of maxillofacial in pediatric patients has some unique considerations. Therefore, this study described the effectiveness of microvascular reconstruction in children with maxillofacial defects.Methods: The relevant literature from PubMed and Science Direct databases. The strategic search is using the keywords such as